Hydrodynamic models of G-quadruplex structures - Chaires, Jonathan B. (Methods Enzymol, 2015)
G-quadruplexes are noncannonical four-stranded DNA or RNA structures formed by guanine-rich repeating sequences. Guanines nucleotides can hydrogen bond to form a planar tetrad structure. Such tetrads can stack to form quadruplexes of various molecularities with a variety of types of single-stranded loops joining the tetrads. High-resolution structures may be obtained by X-ray crystallography or NMR spectroscopy for quadruplexes formed by short (≈25 nt) sequences but these methods have yet to succeed in characterizing higher-order quadruplex structures formed by longer sequences. An integrated computational and experimental approach was implemented in our laboratory to obtain structural models for higher-order quadruplexes that might form in longer telomeric or promoter sequences. In our approach atomic-level models are built using folding principles gleaned from available high-resolution structures and then optimized by molecular dynamics. The program HYDROPRO is then used to construct bead models of these structures to predict experimentally testable hydrodynamic properties. Models are validated by comparison of these properties with measured experimental values obtained by analytical ultracentrifugation or other biophysical tools. This chapter describes our approach and practical procedures.